Perbandingan Metode Pengembangan Perangkat Lunak (Waterfall, Prototype, RAD) - Titania Pricillia; Zulfachmi (Jurnal Bangkit Indonesia, 2021)
The System Development Life Cycle or better known as SDLC is a general methodology used to develop information systems. SDLC consists of several phases starting from the planning, analysis, design, implementation to system maintenance phases. The discussion is about the waterfall development method, prototype and rapid application development (RAD). The results of the comparison of the three models state that the waterfall model is more suitable for generic systems or software, while prototype and RAD are more suitable for customized systems or software. According to the analysis obtained, the three methods have their respective advantages and disadvantages, so that developers can choose which method is more suitable for software development.